Drogi afirmacji Boga (3) - The ways of the affirmation of God (3) - Zdybicka, Zofia (Zielona Góra: Uniwersytet Zielonogórski)
The author resumes her deliberations on the way of affirming God, reflecting on the history of knowledge about God in philosophy.
Keywords: filozofia; teologia; kultura